Kriteria Buku Ajar Bahasa Arab; Studi Literatur terhadap Berbagai Analisis Buku Ajar - Khoir, Nashirul; Karim Amrullah, Abdul Malik; Arifah, Zakiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and map the criteria commonly used in a comprehensive overview so that they can serve as a reference and facilitate other researchers who wish to conduct research using textbook criteria as an analytical tool or evaluation instrument. This study is a literature review based on Krippendorff’s content analysis model, employing a descriptive-analytical approach, aimed at examining, identifying, and synthesizing research related to textbook suitability criteria across various scientific articles on the content analysis of Arabic textbooks in Indonesia from 2021 to 2025. The results indicate a diversity of standards in the analysis of Arabic textbooks in Indonesia, categorized into three main orientations. First, the dominance of BSNP/BSKAP criteria reflects a general and administrative national evaluation approach. Second, the use of Mackey and ACTFL perspectives signifies a shift toward a pedagogical approach focused on the learning process and communicative competence. Third, the approaches of Al-Fauzan and Thuaimah offer a more specific integrative model within the tradition of Arabic language teaching by comprehensively combining linguistic, cultural, and pedagogical aspects. However, there are several articles that use criteria that are unclear or not well-defined